Tinjauan Literatur Mengenai Perceraian dalam Hukum Islam: Sebab dan Konsekuensinya - Nurmayani Nurmayani; Siti Zahara; Cinta Febby Dewita; Indri Wahyuni; Putri Khairi Izwani; Muhammad Rizky Pratama6 (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Divorce is a complex social phenomenon with significant impacts on families, especially children. In Islamic law, divorce is permitted as a last resort when household life cannot be maintained, although it is considered the most hated lawful act by Allah. This study analyzes divorce from the perspective of Islamic family law, focusing on the causal factors, legal impacts, and preventive measures. The main factors of divorce include disharmony in relationships, economic problems, the presence of a third party, and domestic violence. The legal impacts include child custody, division of property, and maintenance obligations, which are often not fulfilled by the ex-husband, causing inequality in legal protection for women and children. Recommended preventive measures include premarital education, family counseling based on Islamic values, and strengthening mediation institutions such as BP4. This study uses qualitative methods with literature analysis to provide a comprehensive understanding of divorce in Islamic law and its implications in Indonesia.